2005
DOI: 10.1007/bf02430411
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the thickness of sputter-deposited platinum films on the electrochemical promotion of propane combustion

Abstract: Abstract.8 to 120 nm-thick Pt coatings were sputter-deposited on Yttria-Stabilised Zirconia (YSZ) membranes, 17 mm in diameter, by magnetron sputtering of a Pt target at low pressure (0.3 Pa). The catalytic activity of propane combustion under open-circuit conditions is first measured near to the stoichiometry (0.2%C3H8/1%O2) and shows that the coatings present a rather high catalytic activity. Close-circuit measurements were finally performed at 337 ~ and 400 ~ They show that rather high faradaic efficiencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…When the current was stopped, the conversion returned to its initial value. The rapid response of activity with applied overpotential is characteristic of sputtered catalytic thin films as already shown in a previous paper [25]. These results confirm the inhibiting effect of ionic species on propene conversion.…”
Section: Light-off Curvessupporting
confidence: 87%
See 1 more Smart Citation
“…When the current was stopped, the conversion returned to its initial value. The rapid response of activity with applied overpotential is characteristic of sputtered catalytic thin films as already shown in a previous paper [25]. These results confirm the inhibiting effect of ionic species on propene conversion.…”
Section: Light-off Curvessupporting
confidence: 87%
“…This technique creates reproducible and dense films for EPOC applications [24]. Propene oxidation was investigated in lean-burn conditions (large excess of oxygen) and at low temperatures (260°C) in order to simulate the operating conditions of a real Diesel exhaust gas [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, thin films of Pt were sputter-deposited by magnetron sputtering of a Pt target on two different solid electrolytes: 8 mol% Y 2 O 3 -stabilized ZrO 2 (YSZ), an O 2) ionic conductor and Na 3 Zr 2 Si 2 PO 12 (NASICON), a Na + one. We have shown in previous studies [11,12] that magnetron sputtering is a suitable technique for synthesis of catalyst coatings. The development of electrochemical catalysts composed of a very thin layer of sputtered catalyst onto a solid electrolyte can considerably reduced the Pt loading.…”
Section: Introductionmentioning
confidence: 98%
“…The results were in good qualitative agreement with the model predictions [84] describing the diffusion and reaction of the backspillover O 2-species, which causes the EP. In previous study [85] the influence of the thickness of sputter-deposited Platinum films on the Electrochemical Promotion of propane combustion was studied by Billard and Vernoux. They found that the catalytic activity does not follow a linear evolution with the film thickness while NEMCA measurements performed at 337°C and 400°C indicate that a minimal thickness of about 15 nm is required in order to allow the bias of the whole Pt surface.…”
Section: Electrochemical Promotion Of Reactions With Environmental Anmentioning
confidence: 99%